The Legal Protection for Parties in Making E-Notary-Based Authentic Deeds during the Covid-19 Pandemic - Astuti, Dea; Wahyuningsih, Sri Endah (Jurnal Konstatering, 2022)
This study aims to analyze the need for authentic e-notary-based deeds during the COVID-19 pandemic and to find out legal protection for parties in making e-notary authentic deeds during the COVID-19 pandemic. The method used in this study is a sociological juridical analysis method, namely a review based on applicable laws and regulations with phenomena that develop in society. The results of the study show that E-Notary during the COVID-19 pandemic is very necessary to protect the notary and the public from the threat of the virus and aims to protect against document falsification. The application of the cyber notary concept in Indonesia is very necessary to anticipate other emergencies that cannot be predicted in the future. The protection of the parties in making an authentic deed based on e-notary has not been specifically regulated in positive law in Indonesia, so that the deed made is not in accordance with the provisions of the authentic deed as regulated in Article 1868 of the Civil Code and the Law on Notary Positions No. 2 of 2014 specificall in Article 38 UUJN and Article 16 paragraph (1) letter m UUJN then the strength of the notary deed does not have perfect proof like an authentic deed, it does not meet the requirements for the authenticity of a deed. Until now, electronic deeds are only considered as private deeds which are equivalent with documents, letters, and electronic certificates.